Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve [tex]3x - 9 \geq 27 - 6x[/tex]

A. [tex]x \geq 4[/tex]

B. [tex]x \leq 4[/tex]

C. [tex]x \leq -12[/tex]

D. [tex]x \geq -12[/tex]


Sagot :

To solve the inequality [tex]\(3x - 9 \geq 27 - 6x\)[/tex], follow these detailed steps:

1. Start with the given inequality:
[tex]\[ 3x - 9 \geq 27 - 6x \][/tex]

2. Move all terms involving [tex]\(x\)[/tex] to one side of the inequality:
To simplify, add [tex]\(6x\)[/tex] to both sides of the inequality:
[tex]\[ 3x - 9 + 6x \geq 27 \][/tex]

3. Combine like terms:
Combine the terms with [tex]\(x\)[/tex] on the left side:
[tex]\[ 9x - 9 \geq 27 \][/tex]

4. Isolate the term with [tex]\(x\)[/tex]:
To isolate [tex]\(x\)[/tex], add [tex]\(9\)[/tex] to both sides of the inequality:
[tex]\[ 9x - 9 + 9 \geq 27 + 9 \][/tex]
[tex]\[ 9x \geq 36 \][/tex]

5. Solve for [tex]\(x\)[/tex] by dividing both sides by 9:
[tex]\[ \frac{9x}{9} \geq \frac{36}{9} \][/tex]
[tex]\[ x \geq 4 \][/tex]

Therefore, the solution to the inequality [tex]\(3x - 9 \geq 27 - 6x\)[/tex] is [tex]\(x \geq 4\)[/tex].

So the correct answer choice is:
A. [tex]\( x \geq 4 \)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.